Learning Needs Analysis: Thematic Teaching Book Based on HOTS Assisted with 3D Stereoscopic Images to Improve Critical Thinking Ability of Elementary School Students - Permana, Dede; Utomo, Utomo (Universitas Malikussaleh, 2021)
This study is descriptive explorative which aims to see the needs of teachers and students in implementing High Order Thinking Skills (HOTS) based learning in thematic learning. The research objectives were achieved through observation, interviews and document study. The results of observations show that in learning students have problems with learning interest, this can be seen when students do activities that are not related to learning. Meanwhile, the results of the interviews which were supported by document study data revealed that in the thematic book the conceptual presentation was not given in depth. It is necessary to add various activities that support the student learning process. In addition, the teacher argues that it is necessary to provide pictures as an illustration of the teaching concept given, this is because elementary school students are in the 7-11 year age range who are still in the concrete operational thinking stage which requires textbooks that can present abstract concepts. concretely. Based on this, it is natural that students are not interested in participating in learning. This study concludes that the thematic textbooks currently used have shortcomings in the presentation of HOTS material and supporting activities. To cover these shortcomings, it is necessary to develop thematic books that have a more complete concept of material and are made according to the characteristics of elementary school students and contain various activities to support HOTS ability improvement. The development of textbooks is needed as an effort to increase learning interest so that learning objectives can be maximally achieved.